PENGEMBANGAN PEMBINAAN PRESTASI OLAHRAGA FUTSAL KABUPATEN BANGGAI (Banggai Regency Experiment Study) - MUHAMMAD SALAHUDDIN; ARMIN HALUTI; NURHIKMAH NURHIKMAH (JURNAL PENDIDIKAN GLASSER, 2020)
Banggai regency futsal sport is quite well known among the people, but not futsal athletes have been able to compete at the provincial or national level such as in the provincial sports championship (Porprov) held in Moutong in 2019. Eventhough seeing futsal athletes when participating in the championships that held in the district many athletes who have talent, skill, and good ability in playing futsal. But this futsal development especially the futsal district association (AFKAB) has not shown achievements. The purpose of this research is to find out: the quality of athletes, coaches, training programs, organizations, facilities and infrastructure, funding for the Banggai Regency Futsal Association. This research was conducted in Banggai Regency, Central Sulawesi. The method used in this research is a qualitative method using questionnaire or questionnaire. The results of this resarch in the classification of the quality of futsal athletes in Banggai Regency the frequency of futsal athletes in Banggai Regency is classified as Good with criteria of 17 people or 51.5% of 33 athletes. The quality of the trainers is quite poor with a frequency of 2 people or 66.7% of the 3 trainers. The quality of the training program is quite poor with a frequency of 2 people or 66.7%. The quality of the organization is good with a frequency of 3 people or 60% of 5 management. The quality of facilities and infrastructure is classified as poor in terms of athletes, trainers and administrators. The quality of funding is classified as good with a frequency of 3 people or 60% of 5 management. The quality of athletes in fostering Futsal sporting achievements in Banggai Regency is included in good criteria, seen from the spirit of training and athletes' efforts in achieving optimal performance. The conclusion of this study: the quality of athletes, administrators and funding is good while the quality of trainers, training programs, facilities and infrastructure is still not good in fostering futsal achievement in Banggai Regency. So the development of futsal sporting development in Banggai Regency needs to get special attention for the trainers, facilities and infrastructure of the KONI management and the Government.